The Role of Parentese in First Language Acquisition: A psycholinguistic Study - Sudartinah, Titik (English Education Department, Universitas Islam Indonesia, 2008)
This paper discusses one of the major topics in psycholinguistics, language acquisition. It describes how children learn and acquire their first language, as well as the factors affecting the acquisition. Parentese and baby talk, among many other factors, are unique in their nature and characteristics. There are some benefits of using parentese in relation to language learning: children develop more vocabulary, understand abstract concepts easier, learn grammar naturally, and understand conversation routines.